Implementation of the use of Google Form media as an Instrument of Learning Evaluation in Arabic Writing Skills: A Case Study in Madrasah Aliyah Terpadu Al Hidayah Sumenep - Zufrufin Saputro; Ribut Wahyu Eriyanti; Hari Sunaryo (Electronic Journal of Education, Social Economics and Technology, 2025)
This research was conducted to explore the use of Google Form in assessing Arabic writing skills. This qualitative study was carried out at MA Terpadu Al Hidayah Sumenep, with tenth-grade students in the 2024/2025 academic year as subjects. The research findings revealed that utilizing Google Form for evaluating Arabic language learning, particularly in the aspect of writing skills (maharah kitabah), offers significant advantages. The primary benefits include making it easier for teachers to grade assignments, while also saving time and effort. Furthermore, the use of Google Form successfully boosted students' motivation and enthusiasm in completing evaluation tasks. Beyond that, the implementation of this technology also supports efforts to reduce paper consumption, reflecting a commitment to environmental concerns. Although some challenges were encountered, such as errors in form submission, these were viewed as opportunities for students to continue developing their writing abilities.